Corn Agronomic Attributes in Succession of Leguminous Cover Crops and Nitrogen Doses - Cieslik, Laures Francisco; Conceição, Paulo Cesar; Oliveira, Jaqueline Pereira Machado de; Ziech, Ana Regina Dahlem; Stumpf, Lizete; Freitas, Leandro Alves de (Journal of Agricultural Studies, 2021)
This study aimed to determine the dry biomass and nitrogen accumulation, the height and stem diameter of corn crop preceded by different leguminous cover crops, under different nitrogen doses. The study was conducted in the experimental area of Federal Technology University of Paraná, in Dois Vizinhos. The eigth cover crops consisted on: Sunn hemp; Crotalaria spectabilis; Jackbean; Cajanus cajan; Dolichos lablab; Velvet beans; Black velvet beans and Spontaneous species. The two dose nitrogen fertilization included: zero kg N ha-1; 180 kg N ha-1 applied in a single dose, under conditions of adequate humidity, 47 days after corn seeding. Were evaluated the height, dry biomass and basal stem diameter corn and the decomposition and release of N from the cover plants. The use of leguminous before corn crop is a good option for the southwest region of Paraná because it promotes soil protection and can promote increased carbon stock in the environment. The leguminous cover crop should be used like green manure, making them important species in the Brazilian agriculture sustainability context, once there are evidence of reducing or even not using mineral nitrogen fertilization in the subsequent agricultural crops, mainly the Jackbean.